Democracy [compact disc, unabridged] : stories from the long road to freedom - Rice, Condoleezza, 1954- (Hachette Audio, 2017)
Traces key events, witnessed by the author, throughout the past fifty years, assesses the evolution of global democracy, and discusses how it is under attack throughout the world.